2019
DOI: 10.1158/2159-8290.cd-18-0606
|View full text |Cite
|
Sign up to set email alerts
|

EIF1AX and RAS Mutations Cooperate to Drive Thyroid Tumorigenesis through ATF4 and c-MYC

Abstract: Translation initiation is orchestrated by the cap binding and 43S preinitiation complexes (PIC). Eukaryotic initiation factor 1A (EIF1A) is essential for recruitment of the ternary complex and for assembling the 43S PIC. Recurrent EIF1AX mutations in papillary thyroid cancers are mutually exclusive with other drivers, including RAS . EIF1AX mutations are enriched in advanced thyroid cancers, where they display a striking co-occurrence with RAS , which cooperates to induce tumorigenesis in mice and isogenic cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 65 publications
5
52
0
1
Order By: Relevance
“…A similar approach was performed in PDTC and ATC [55]. Notably, functional studies demonstrated that EIF1AX mutations cooperate with RAS in inducing thyroid tumorigenesis and sensitize tumor cells to mTOR inhibition [57].…”
Section: Molecular Alterations and Therapeutic Implicationsmentioning
confidence: 99%
“…A similar approach was performed in PDTC and ATC [55]. Notably, functional studies demonstrated that EIF1AX mutations cooperate with RAS in inducing thyroid tumorigenesis and sensitize tumor cells to mTOR inhibition [57].…”
Section: Molecular Alterations and Therapeutic Implicationsmentioning
confidence: 99%
“…Mutations affecting EIF1AX, which participate in the onset of translation, has no influence on metastases and more work is needed to establish possible relations between both (86). Of note, EIF1AX mutations seem to exert a synergistic effect on Ras mutations in certain types of tumours, such as ovary and thyroid (93,94). The low proportions of uveal melanoma cell mutations in these genes may explain why EIF1AX is not associated with a greater metastasis risk in the tumours.…”
Section: Biology Of Uveal Melanomamentioning
confidence: 99%
“…EIF1AX mutations are common in advanced thyroid cancers, accompanied by a simultaneous occurrence of RAS mutations. The cooperation of EIF1AX and RAS mutations can induce the formation of tumors in mice [18]. The co-occurrence and subsequent co-expression of mutant NRAS and EIF1AX promoted proliferation and survival in ovarian low grade serous carcinomas [19].…”
Section: Eukaryotic Translation Initiation Factor 1 (Eif1)mentioning
confidence: 99%